Strategi World Wide Fund For Nature dalam Menekan Perdagangan Ilegal Satwa Liar di Indonesia Tahun 2018 - Muhammad Fadel Narendra; Mahdi, Imam (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This research discusses WWF's strategy in suppressing illegal wildlife trade in Indonesia in 2018. Indonesia occupies the highest position regarding illegal wildlife trade cases compared to other countries in the world, especially in the 2015-2017 period. WWF considers this problem to be a serious phenomenon that must be resolved through concrete actions. In 2018, WWF launched the “Stop! Illegal Trade in Wild Animals," via the WWF Indonesia YouTube channel in collaboration with all related parties. The theory used in this research is the Non-Governmental Organization Concept. This theory emphasizes that NGOs have two main functions, namely Operational NGOs and Advocacy NGOs, where these two functions are closely related to each other in terms of implementation. The research method used is descriptive qualitative, with data collection through library research, namely collecting resources from books, journals, theses, articles, papers, research reports, press releases and news that are relevant to this research. This research found that WWF has succeeded in suppressing the illegal trade in wildlife in Indonesia through collective campaigns and collaboration with related parties.